Computational modelling of structural batteries accounting for stress-assisted convection in the electrolyte. (1st March 2022) - Carlstedt, David; Runesson, Kenneth; Larsson, Fredrik; Tu, Vinh; Jänicke, Ralf; Asp, Leif E.
Abstract: Structural batteries consist of carbon fibres embedded in a porous structural battery electrolyte (SBE), which is composed of two continuous phases: a solid polymer skeleton and a liquid electrolyte containing Li-salt. In this paper we elaborate on a computational modelling framework to study the electro-chemo-mechanical properties of such structural batteries while accounting for the combined action from migration as well as stress-assisted diffusion and convection in the electrolyte. Further, we consider effects of lithium insertion in the carbon fibres, leading to insertion strains. The focus is placed on how the convective contribution to the mass transport within the SBE affects the general electro-chemo-mechanical properties. The numerical results indicate that the convective contribution has only minor influence on the multifunctional performance when the mechanical loading is caused by constrained deformation of constituents during electro-chemical cycling. However, in the case of externally applied mechanical loading that causes severe deformation of the SBE, or when large current pulses are applied, the convective contribution has noticeable influence on the electro-chemical performance. In addition, it is shown that the porosity of the SBE, which affects the effective stiffness as well as the mobility and permeability, has significant influence on the combined mechanical and electro-chemical performance.